Economic relations between Latin America and the European Union - Roberto Smith Perera (CEPAL Review, 1995)
Two opposing trends are currently shaping relations between the European Union and Latin America. On the one hand, political signals in both regions are positive and point the way to closer ties in the future; on the other hand, the situation with regard to the Union’s trade with Latin America has worsened appreciably, with the region’s trade surplus giving way to a deficit for the first time in four decades. This trend may jeopardize the progress made thus far. If we do not act now, trade-related tensions, the reduction of development assistance and the appearance of social or environmental trade restrictions may cast a shadow over the bilateral situation, causing the two regions to become what we might describe as distant friends.